Small Incision Lenticule Extraction (SMILE) Principles, Techniques, Complication Management, and Future Concepts - Sekundo, Walter (Springer International Publishing : Imprint: Springer, 2015)
In this book an international panel of authors offer a clear, step-by-step approach to Small Incision Lenticule Extraction (SMILE), a novel refractive procedure approved for the treatment of myopia and astigmatism. The book opens by discussing important fundamentals of the technology, followed by a close look at the healing response. The current surgical techniques are then described in detail with the aim of providing easy-to-understand guidance for all who wish to perform SMILE surgery or to identify solutions to pitfalls that may arise during the learning curve. A section on clinical science is aimed at the more advanced reader who wants to understand the underlying principles of SMILE surgery; it provides a clear knowledge of the advantages of the procedure and ways to improve results. Ongoing investigations to further expand the spectrum of SMILE surgery are then examined, with coverage of hyperopia treatment, reversible refractive surgery, and surgery for very high myopia. Finally, suggestions are offered on how to market this advanced procedure and communicate it to the prospective patient.